(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2014)
The plants of Orchis picta Loisel.collected in Chornomorski Biosferical Reserve were observed. The infectivity of plant sap and viral capability to transmit in mechanical manner were confirmed. The spherical particles with diameter about 50 nm and 80-100 nm were observed in preparations from test-plants’ symptomatic leaf in transmission electron microscope. According to viral morphology these pathogens of O. picta may be members of Caulimoviridae and Tospovirus respectively.